(untitled) (Current Problems in Rail Vehicles, 2021)
The system which increases high operating durability by its pneumatic way of solution and avoids onetime and continual souring of sand by all activated or inactivated sand storages above defined limits. It means enormous or insufficient sanding. Technical solution does not allow pouring of higher amount of sand into area of contact between a wheel and a rail in case of malfunction of pneumatic system of a vehicle. Universal character of the device allows its application in modest modifications for all rail vehicles. This sanding device is mounted gradually on new and reconstructed driving vehicles.